Modeling Air Pollution Due To Forest Fire. - Gooi, Bee Sung; Koh, Hock Lye; Md Ismail, Ahmad Izani (Penerbit Universiti Sains Malaysia, 2005)
Air pollution has long been a masjor environmental concernin many countries.The major sources of air pollution are vehicles exhausts,open burning and emission from industrial stacks and power generation stations as well as forest fires.Air pollution poses hazards to human health,poison rivers and lakes, damages trees and kills wildlife. Major pollutants are carbon monoxide,sulphur dioxide,nitrogenoxides and particulate matters. Forest fire is a large scale,unenclosed and free spreading natural combustionprocess that consumes various ages,sizes and types of vegetative matter of the forest.